Ayurvedic Management of Artava Kshaya (International Journal of Ayurveda and Pharma Research, 2025)
Gynecological problems are rising quickly in today's fast-paced and competitive world due to sedentary lifestyles, poor eating habits etc. The menstrual cycle is significantly impacted by changes in both physical and mental health. Menstrual disorders are becoming more common in gynecological practices, which is a sign of infertility and other issues. One prevalent menstruation disorder is Artava kshaya (oligomenorrhoea). As, Artava is Updhatu of Rasa dhatu and modification in Ahara leads to Dushti of Rasa lead to Artava dushti leading to Artava kshaya. Case Report: A female patient of 20 years of age came to OPD of SDACH, Chandigarh, on 25th November 2023 with chief complaint of delayed menstruation with scanty flow since 6 months. Methodology: Detailed history with all necessary clinical, physical examination and laboratory investigations were carried out. No gross physical and chemical abnormality was found. All the laboratory investigations (including USG and hormonal analysis) were found to be normal. So, the treatment was planned according to the symptoms. Diagnosis was made on the of presenting complaints which was Artava kshaya (oligomenorrhoea). Patient was treated with Nasthapushpanthak Rasa and Krishana Tila Kwath along with diet and lifestyle modification for 3 consecutive cycles. Patient was kept on follow up for 3 cycles after cessation of all medications. Result: Patient had got her menstruation regularly with normal duration while taking medicine. Also, the amount of flow was also improved and intensity of pain was reduced effectively from moderate to mild. Even after cessation of medicine she got her menstruation in 32 days with normal amount of flow.